TREN PERUBAHAN CROP WATER PRODUCTIVITY KAKAO (Theobroma cacao L. ) DI D.I. YOGYAKARTA - Eka Suhartanto; Lisma Safitri (The University of Lampung, 2020)
The studies on the Crop Water Productivity (CWP) of cocoa to increase productivity in the midst of water scarcity and climate change are currently underdeveloped. Thus, this study aims to find out the trends in climate, productivity, crop water use and CWP of cocoa plantations. The methods included collecting climate and productivity data during 2014-2019, simulating crop water use with Cropwat 8.0 software and analysing the changing trends of CWP in cocoa plantations, DI Yogyakarta. The results indicated the changes in productivity of cocoa plantation ranged from 0,41 – 0,53 tons / ha. The Crop Water Usage (CWU) decreased from 11.107 m3 in 2014 to 8.482 m3 in 2019 under rainfed schenario. Subsequently, the trend of CWP tended to increase from 0,037 kgm-3 in 2014 to 0,059 kgm-3 in 2019. CWP of cocoa plantation increased when CWU decreased and productivity increased. CWP value illustrated that every 1 m3 of water used have produced 0,037 – 0,059 kg of dried cocoa beans. In terms of water use efficiency, this relatively small CWP value indicates that the level of water use by cocoa plants in DI Yogyakarta is inefficient that requires improvement in the future such as increasing land productivity and precision irrigation schemes for cocoa plantations. Keywords: Cacao (Theobroma cacao L.), crop water productivity, crop water use, D.I Yogyakarta